2015
DOI: 10.1021/acs.energyfuels.5b00897
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Characterization of Sulfur Compounds in Ultra-deep Formation Crude Oils from Tarim Basin

Abstract: Sulfur compounds in two representative deep crude oils (Ha9, 6598−6710 m; ZS1C, 6861−6944 m) with distinct levels of maturity from Tarim Basin, China, were analyzed by positive-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The thiophenic and sulfidic compounds were selectively separated from the crude oils with high purity and recovery by the methylation/demethylation approach and further characterized in detail by gas chromatography (GC) coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…The mechanism shown in Figure 7b can also be used to explain the formation of the thiaadamantane by recyclization of the cage-opened adamantanethiol by the attack of −SH to the "red" carbon atom in "pseudo" adamantanethiol. Thiadiamondoids are reliable molecular indicators for the occurrence and extent of TSR, 24,26,42,57,58 which are gradually enriched in 34 S toward sulfur isotopic composition of coexisting sulfate minerals with increasing TSR. 10 The concentration of thiadiamondoids in the ZS1C oil reaches up to 28 000 μg/g, which is much higher than in other crude oils.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism shown in Figure 7b can also be used to explain the formation of the thiaadamantane by recyclization of the cage-opened adamantanethiol by the attack of −SH to the "red" carbon atom in "pseudo" adamantanethiol. Thiadiamondoids are reliable molecular indicators for the occurrence and extent of TSR, 24,26,42,57,58 which are gradually enriched in 34 S toward sulfur isotopic composition of coexisting sulfate minerals with increasing TSR. 10 The concentration of thiadiamondoids in the ZS1C oil reaches up to 28 000 μg/g, which is much higher than in other crude oils.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, , a selective separation method for characterization of thiophenic and sulfidic compounds in petroleum was developed. However, it was found that thiols interfere with sulfides in the methylation/demethylation process by generating methyl sulfides (see Scheme S-1 in Supporting Information).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The results suggested that thiophenes and sulfides had been successfully separated into different fractions. The same research group also used this approach to study sulfur-containing compounds in two crude oils obtained from Tarim Basin, China . These two crude oils were concluded to contain different biomarker-like sulfur compounds, such as 1,1-dimethylhexahydro-dibenzothiophenes and thiadiamondoids.…”
Section: Applicationsmentioning
confidence: 99%
“…The same research group also used this approach to study sulfur-containing compounds in two crude oils obtained from Tarim Basin, China. 97 These two crude oils were concluded to contain different biomarker-like sulfur compounds, such as 1,1-dimethylhexahydro-dibenzothiophenes and thiadiamondoids. More recently, based on results obtained using (+) ESI Orbitrap Fusion, Wang et al reported that methylation of sulfides and thiophenes into methyl sulfonium salts forms side products that could lead to incorrect assignment of sulfur-containing compounds.…”
Section: Sophisticated Instrumentation Requiredmentioning
confidence: 99%